ESTETIKA BENTUK KURSI TAMAN PADA KAWASAN CITY WALK KOTA SURAKARTA - Henny Tri Hastuti Hasana (Canthing, 2020)
The Scientific Journal with the title "Aesthetics of the Form of Park Chairs in the Surakarta City Walk Area," focuses on the subject matter regarding the shape of city park chairs on Jalan Slamet Riyadi Surakarta if examined aesthetically. The purpose of this study is to discuss and explain the shape of the Surakarta city park road chair which is studied by discussing aesthetics. The steps (methods) of research use quality research methods. The location of the study was conducted in the city walk area of Surakarta City. Data obtained through observation, interviews, and documents (archives). Data analysis uses interaction analysis and interpretation analysis. Conceptually, the form and structure of conclusions. The results showed the shape of the Surakarta city park road chair with structure as an aesthetic element. Garden street chair ornaments, as decorations that support the beauty of the chair shape. The motifs that form passive ornaments, this is independent of ornament ornaments as a symbolic meaning.